2001
DOI: 10.1128/jcm.39.7.2742-2744.2001
|View full text |Cite
|
Sign up to set email alerts
|

Endophthalmitis Caused by Listeria monocytogenes

Abstract: Listeria monocytogenes was isolated from the aqueous chamber of an immunodepressed patient with acute hypertensive uveitis, who developed a dark hypopyon and pigment dispersion. No extraocular septic focus was found. Treatment was successful with intravitreal vancomycin, anterior chamber irrigation with vancomycin, orally administered ciprofloxacin, and topical fortified vancomycin. CASE REPORTA 62-year-old man presented to the emergency department with pain, redness, and decreased vision in the left eye. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
38
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 24 publications
0
38
0
5
Order By: Relevance
“…In addition, it has been noted that most ruminant cases of listerial ocular infections appear to occur in the winter and early-spring months, when the animals are housed inside and fed silage. 7,14,16 Although single cases of listerial eye infections have been described previously, 1,7,14,16 this report represents a more comprehensive review of Listeria infections in animals reported in New York State to probe case histories and microbiological and molecular characteristics associated with L. monocytogenes infections of the eye.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, it has been noted that most ruminant cases of listerial ocular infections appear to occur in the winter and early-spring months, when the animals are housed inside and fed silage. 7,14,16 Although single cases of listerial eye infections have been described previously, 1,7,14,16 this report represents a more comprehensive review of Listeria infections in animals reported in New York State to probe case histories and microbiological and molecular characteristics associated with L. monocytogenes infections of the eye.…”
mentioning
confidence: 99%
“…Although only few records of naturally occurring ocular infections by L. monocytogenes exist, 1,5,7,13,14,16 the ability of L. monocytogenes to cause conjunctivitis and keratitis has been well established in experimental animals. 4,8,9,12 In fact, the development of conjunctivitis and corneal infection in rabbits was once used as a method of confirming the identification of an infectious culture as L. monocytogenes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…En pacientes inmunodeprimidos o UDVP se aíslan Candida spp. 10 , Aspergillus spp con elevada mortalidad 17 y otros hongos filamentosos 18 , Listeria monocytogenes 19 o Bacillus cereus, principalmente en UDVP por contaminación de la solución utilizada para inyectarse la droga 1 .…”
Section: Discussionunclassified